Portraying the Learning Needs of English Language in Non-English Department Students - Mardianti, Nunung; Dwipa, Lalu Belik Made (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The existence of English language courses plays an important role in efforts to welcome industry 4.0. This is caused by the use of English which dominates knowledge and science and even today's lifestyle. Thus, in the implementation of teaching, English has been taught from low level education to high level education. Learning English at the college level non-English majors have different needs than English majors. Primary School Teacher Education (PGSD) is present as one of the non-English majors and has a curriculum that requires students to master English, especially for research needs, articles, teaching materials and books and other sources written in English. This is because education departments have already developed in countries that use English and Latin as their national languages. It can be emphasized that some of the learning materials and resources written in books, articles and journals related to the field of PGSD are written in English and Latin. So that through needs analysis, lecturers and students can find out which aspects of language skills and competencies must be mastered to support the scientific field they are pursuing. Through the results of the analysis, lecturers can also determine what teaching methods, media and materials are in accordance with the learning objectives that have been formulated.